Veil in the Letter Al-Ahzab Verse 59 and Its Relevance to Islamic Education - Disa, Wa; Rahim, Abdul; Yahya, Safaruddin (Journal of English Language and Education, 2025)
The purpose of this essay is to examine the Islamic obligation to wear the hijab and the phenomenon of the refusal of some Muslim women to follow Islamic law. This study combines the methodology of literature study with qualitative methods. Wearing the hijab is strictly required by Islam as part of the full implementation of religion. However, in practice, many Muslim women have not adopted Islamic law as a way of thinking and behaving, especially in the realm of education. The findings of this study indicate that the prevalence of a secular mindset and poor understanding of Islamic teachings in general are the main causes of this non-compliance. Therefore, great efforts are needed in the world of Islamic education that not only emphasizes theoretical and legal aspects, but also forms an ideological awareness of the importance of making Islam the only guideline for life.